Radix entomolaris with "three distal canals:" A rare case report - Srilekha Jayakumar; Nandhini Ambalavanan; Ramaprabha Balasubramanian; Anbarasu Subramanian (Wolters Kluwer Medknow Publications, 2022)
The intricate and atypical morphology of mandibular molars makes root canal therapy challenging both in diagnosis and during clinical procedure. The clinician should have knowledge on precise nature of the root canal structure and morphology. Better understanding allows good cleaning, shaping, and disinfection of the canal space, followed by its three-dimensional obturation. This paper illustrates the management of radix entomolaris with "three distal canals" in first mandibular molar - a rare entity.